International Scholarships in Higher Education Pathways to Social Change (Springer International Publishing, 2018)
This book maps and analyzes the multiple pathways from international scholarships to positive social change. It brings together the contributions of academic researchers, evaluators, and scholarship professionals from Africa, Asia, Latin America, the US, Europe, and Australia to create a dialogue on the present and future of international scholarship programs. The issues addressed in this volume include the alignment between scholarships and other development oriented education programs; the complexities of selecting 'leaders'; the dynamics of returning home and concerns about brain drain; and the state of knowledge and research on long-term outcomes of international scholarships with social change aims. The book is intended for readers from higher education, practitioner, and policy communities around the world, and especially for those who work at the nexus of higher education and development.